2019
DOI: 10.1186/s41938-019-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of the entomopathogenic fungus, Beauveria bassiana (Bals.) Vuill. endophytic and a soil isolate against the squash beetle, Epilachna chrysomelina (F.) (Coleoptera: Coccinellidae)

Abstract: Laboratory and field bioassays were conducted to evaluate the pathogenicity of an endophytic and a soil isolate of the entomopathogenic fungus, Beauveria bassiana (Bals.) Vuill. against different stages of squash beetle, Epilachna chrysomelina (F.) (Coleoptera: Coccinellidae). Both isolates were identified by ITS rDNA sequence analysis. Both isolates were pathogenic to the squash beetle; however, their potential was different according to the conidia concentration and the exposure period. Three days post treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…We observed a lesser number of adult male moths, and female moths had some apparent alterations in their wings. This result is in agreement with Hassan et al [39], who reported that malformations occurred in B. bassiana-treated squash beetles. Interestingly Russo et al recently reported differences on Spodoptera frugiperda's female fertility, fecundity and longevity using corn plants endophytically-inoculated with B. bassiana by foliar spray treatments; although in contrast, they did not find significant differences in the sex ratio of Helicoverpa gelotopoeon when they were fed on B. bassiana treated soy bean plants [40].…”
Section: Discussionsupporting
confidence: 93%
“…We observed a lesser number of adult male moths, and female moths had some apparent alterations in their wings. This result is in agreement with Hassan et al [39], who reported that malformations occurred in B. bassiana-treated squash beetles. Interestingly Russo et al recently reported differences on Spodoptera frugiperda's female fertility, fecundity and longevity using corn plants endophytically-inoculated with B. bassiana by foliar spray treatments; although in contrast, they did not find significant differences in the sex ratio of Helicoverpa gelotopoeon when they were fed on B. bassiana treated soy bean plants [40].…”
Section: Discussionsupporting
confidence: 93%
“…The second highest isolate caused 83.33% mortality after twelve days. Previous studies have recorded mortalities of 100%, which is incredible, but mortalities of 60% and above are good enough in controlling insect populations [52]. Beauveria bassiana has been an entomopathogen in many insect orders, including Lepidoptera, Hemiptera, Coleoptera, and Diptera, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Collected mites were released in the Petri plate and allowed to multiplication. The cotton pads were moistened daily and the mulberry leaves were changed whenever it is necessary (Hassan et al 2019). After multiplication of the mites, it was transferred to the caged potted bhendi (Bhendi hybrid COBh H 1) plants maintained at Insectary, Department of Agricultural Entomology, Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu for further multiplication.…”
Section: Rearing Of Two-spotted Spider Mites T Urticae For Pathogenic...mentioning
confidence: 99%